2009
DOI: 10.2334/josnusd.51.11
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and periodontal disease

Abstract: 1,25-Dihydroxyvitamin D(3) [1,25(OH)(2)D(3); 1,25-dihydroxycholecalciferol or calcitriol] is the active form of vitamin D(3), a lipid-soluble vitamin that plays a role in calcium and bone metabolism. Recently, vitamin D(3) has been shown to function in cancer prevention, immunity and cardiovascular regulation. 1,25(OH)(2)D(3) exhibits physiological and pharmacological effects by activating the vitamin D receptor (VDR), a transcription factor of the nuclear receptor superfamily. 1,25(OH)(2)D(3) plays a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 69 publications
0
64
0
2
Order By: Relevance
“…Based on this case definition, we found that those consuming ≥ 800 IU/day of total vitamin D had lower odds of having periodontal disease compared with those consuming less than 400 IU/day. The medical literature regards vitamin D deficiency as a risk factor for osteoporosis, which may also affect the jaws (van Schoor et al, 2008;Amano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this case definition, we found that those consuming ≥ 800 IU/day of total vitamin D had lower odds of having periodontal disease compared with those consuming less than 400 IU/day. The medical literature regards vitamin D deficiency as a risk factor for osteoporosis, which may also affect the jaws (van Schoor et al, 2008;Amano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include: bacterial flora, poor oral hygiene, age, sex, diabetes, HIV, pregnancy, menopause, smoking, low socioeconomic status, and local factors (cavities, dental morphology, etc.). Some other general factors are stress, immune deficiency, and nutritional factors, which appear to modulate the body's immune response and determine the level of susceptibility to the disease [5]. The list of these risk factors remains controversial [6].…”
Section: Epidemiological Data In Francementioning
confidence: 99%
“…VDR binds preferentially to a vitamin D response element (VDRE), consisting of a two hexanucleotide (AGGTCA or a related sequence) direct repeat motif separated by three nucleotides (direct repeat 3; DR3), as a heterodimer with isoforms of the retinoid X receptor (RXR), RXRa (NR2B1), RXRb (NR2B2), and RXRg (NR2B3), the receptors for 9-cis retinoic acid [10,20] (see Section II of this volume). DR3-type VDREs have been identified in the regulatory regions of many target genes, including 25-hydroxyvitamin D 24-hydroxylase (CYP24A1), calbindin D9k (CaBP-9k), transient receptor potential vanilloid type 6 (TRPV6), receptor activator of nuclear receptor kB ligand and cathelicidin antimicrobial peptide (CAMP) [2,21,22].…”
Section: The Vitamin D Receptor Is a Dual-functional Receptor For Vitmentioning
confidence: 99%